Swift Development of Protective Effector Functions in Naive Cd8(+) T Cells against Malaria Liver Stages - Sano, Gen-ichiro (The Rockefeller University Press, 2001)
We generated T cell receptor transgenic mice specific for the liver stages of the rodent malaria parasite Plasmodium yoelii and studied the early events in the development of in vivo effector functions in antigen-specific CD8(+) T cells. Differently to activated/memory cells, naive CD8(+) T cells are not capable of exerting antiparasitic activity unless previously primed by parasite immunization. While naive cells need to differentiate before achieving effector status, the time required for this process is very short. Indeed, interferon (IFN)-γ and perforin mRNA are detectable 24 h after immunization and IFN-γ secretion and cytotoxic activity are detected ex vivo 24 and 48 h after immunization, respectively. In contrast, the proliferation of CD8(+) T cells begins after 24 h and an increase in the total number of antigen-specific cells is detected only after 48 h. Remarkably, a strong CD8(+) T cell–mediated inhibition of parasite development is observed in mice challenged with viable parasites only 24 h after immunization with attenuated parasites. These results indicate that differentiation of naive CD8(+) T cells does not begin only after extensive cell division, rather this process precedes or occurs simultaneously with proliferation.